The Evaluation of Implementing the Equality Package Program during the Covid-19 Pandemic in Non-Formal Education Units - Gallex Simbolon; Frans K. Selly; Samrid Neonufa (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
The purpose of this study was to analyze the evaluation of the implementation of the quality of equality programs during the pandemic in the realm of non-formal education. This type of research is a qualitative program evaluation research using a goal base oriented evaluation mode approach which aims to measure the extent to which the goals of formal education have been achieved. The data collection technique in this study used the participant observation technique. The results in this study indicate that based on the evaluation of the context, input, evaluation process and product evaluation of equivalence education package C at PKBM Zaitun, PKBM Oenggae Belajar, PKBM Ita Esa and SPNF Rote Ndao regency are classified as good. However, in the evaluation process it is still considered not good, this can be seen from each PKBM and SPNF in Rote Ndao regency carrying out a predetermined learning process, tutors design their own syllabus and lesson plans, tutors understand the material and learning methods, but in applying the method face-to-face learning, tutorials and independent each PKBM and SPNF have not implemented optimally.